CORRELATION BETWEEN STUDENTS’ METACOGNITIVE STRATEGY USED IN WRITING PROCESS AND ESSAY WRITING PERFORMANCE - Sarah Suci Hartina; Machdalena Vianty; Rita Inderawati (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2018)
Abstract: The aim of this study was to find out whether or not there was any significant correlation between students’ use of metacognitive strategy in writing and their essay writing performance.  Eighty-three sixth-semester students of English Education Study Program of a state university in Palembang got involved in this study. A metacognitive awareness of writing strategy questionnaire and an essay writing test were used as the instruments to collect the data which were analysed statistically by using a correlation nd regression analyses. The finding showed that there was a significant correlation between the students’ use of metacognitive strategy and their essay writing performance. There was also a significant contribution of the metacognitive strategy used to the students’ essay writing performance (70.7%). Keywords: metacognitive writing strategy, essay writing, EFL studnets